101k views
1 vote
-4 (r + 2) = 4 (2 - 2r)

2 Answers

5 votes

Answer:

r=4

Explanation:

User Lukas Eichler
by
4.9k points
4 votes

Answer:

r=4

Explanation:

Let's solve your equation step-by-step.

−4(r+2)=4(2−2r)

Step 1: Simplify both sides of the equation.

−4(r+2)=4(2−2r)

(−4)(r)+(−4)(2)=(4)(2)+(4)(−2r)(Distribute)

−4r+−8=8+−8r

−4r−8=−8r+8

Step 2: Add 8r to both sides.

−4r−8+8r=−8r+8+8r

4r−8=8

Step 3: Add 8 to both sides.

4r−8+8=8+8

4r=16

Step 4: Divide both sides by 4.

4r

4

=

16

4

r=4

Answer:

r=4

User Ivo Velitchkov
by
4.8k points